A Comparison of the Efficacy of Insulin Aspart and Regular Insulin for Managing Gestational Diabetes and their Effects on Delivery Outcomes - Parichehr Pooransari; Atefeh Ebrahimi; Masoumeh Mirzamoradi; Melika Ketabdar (Mashhad University of Medical Sciences, 2021)
Background & aim: Rapid-acting insulin analogs, such as insulin aspart, are used in type 1 and type 2 diabetes in pregnancy, and are approved for using in gestational diabetes mellitus (GDM). Nevertheless, there is a dearth of studies to compare their effectiveness with regular insulin. This study, therefore, compared the efficacy of aspart (NovoRapid) and regular insulin in managing GDM and their effects on delivery outcomes. Methods: This retrospective record review was conducted on 150 pregnant women with GDM who were admitted to Shohada Tajrish Hospital,Tehran, Iran and managed with either insulin aspart or regular insulin (75 patients in  each group). The primary outcomes were insulin dose, hypoglycemic episodes, length of hospitalization at the initiation of insulin therapy, length of insulin therapy, and rehospitalization frequency. The secondary outcomes were delivery and neonatal outcomes. Data was extracted from patients' medical records and analysed using Chi-square, Fisherʼs exact test, t-test, and Mann-Whitney U test. Results: Insulin dose and frequency of hypoglycemic episodes during the first hospitalization for the initiation of insulin therapy were significantly lower in the insulin aspart group. Also, the length of hospital stay and insulin therapy was significantly shorter in the insulin aspart group. In addition, the gestational age at delivery and frequency of normal vaginal delivery were significantly higher in the insulin aspart group. Conclusion: Considering insulin dose, frequency of hypoglycemic episodes as well as length of initial hospital stay, insulin aspart was more efficient than regular insulin in controlling blood glucose in patients with GDM.